2019
DOI: 10.30607/kvj.511340
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melatonin on Some Coagulation Parameters in Streptozotocin-induced Diabetic Rats

Abstract: The aim of this study is to evaluate the possible protective effects of melatonin on hemostatic parameters in diabetic rats. For this purpose, 32 adult, male, healthy Wistar Abino rats were seperated into four groups. Control group didn't exposure any trial. Melatonin group was treated with 50 mg/kg melatonin by intraperitoneally during 8 weeks. In diabetes group, diabetes was induced by subcutaneous injections of streptozotocin at dose of 40 mg/kg for two days as a single daily dose. Diabetes+Melatonin group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…MCV, MCH, MCHC levels did not show any significant alteration. Leukocytes count was increased in diabetic rats; the Neutrophil count was also increased in diabetic group rats (49).…”
Section: Hematologymentioning
confidence: 80%
See 1 more Smart Citation
“…MCV, MCH, MCHC levels did not show any significant alteration. Leukocytes count was increased in diabetic rats; the Neutrophil count was also increased in diabetic group rats (49).…”
Section: Hematologymentioning
confidence: 80%
“…A study carried out by Keskin and et al in 2016 to estimate the beneficial and preventive effects of quercetin on some hematological parameters in streptozotocin-induced diabetic rats. Streptozotocin was injected at a single dose of 60 mg/kg (i.p) for diabetes mellitus induction.…”
Section: Hematologymentioning
confidence: 99%
“…It seems QCN not only by inhibition of CYP2E1 activity and consequently by reduction of BNZ-related metabolites resulted in attenuation of MN percentage in bone marrow and in peripheral erythrocytes, but also increased the RBC number. The possible mechanism for QCN effect on RBC number may be related to its stimulatory effect on erythropoietin secretion [ 31 ]. At the same time, one of the key factors in the pathogenesis of the BNZ-induced toxicity undoubtedly related to its capacity to produce oxidative stress and consequently hematological disorders along with hepatic damages that were characterized by reduction of WBC and RBC numbers and elevation of hepatic enzymes and structural injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that alterations in the hematological parameters of humans, such as lower RBC, HGB, and PLT counts and higher WBC counts, occur with DM [27,28,29]. Several studies have reported reference hematological values for healthy rats [30,31,32], and the same alterations were observed in STZ-induced diabetic rats [33,34]. Consistent with previous data, we observed higher WBC counts and lower RBC, HGB, and PLT counts in the diabetic control rats.…”
Section: Discussionmentioning
confidence: 99%